STUDENTS’ DIFFERENCES AND THEIR OUTCOMES IN ENGLISH LEARNING - Fadillah, Ridha (Universitas Negeri Semarang, 2015)
This paper aims to investigate the students‘ differences and students‘ outcomes in English learning at State Vocational High School 3 (SMKN 3) Purwokerto, Central Java. The samples were second graders at that school. They were 177 fifteen to nineteen year old students. The results indicated that the students‘ both English learning motivation and English language anxiety were at moderate level. There was significant negative relationship between motivation and outcome, but positive correlation between students‘ anxiety and outcome was indicated. It showed that although the students‘ anxiety was high, their learning outcome was till good.